Materials Chemistry of Fullerenes, Graphenes, and Carbon Nanotubes - Chiang, Long Y; Cirillo, Giuseppe (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue is intended as a platform for interactive material science articles with an emphasis on the preparation, functionalization chemistry, and characterization of nanocarbon compounds, as well as all aspects of physical properties of functionalized, conjugated, or hybrid nanocarbon materials, and their associated applications. Some recent advances in the field are here collected, providing new ideas for discussion of researchers working in this multidisciplinary scenario.